Effects of exosome-mediated delivery of myostatin propeptide on functional recovery of mdx mice. (April 2020) - Ran, Ning; Gao, Xianjun; Dong, Xue; Li, Junjin; Lin, Caorui; Geng, Mengyuan; Yin, HaiFang
Abstract: Duchenne muscular dystrophy (DMD) is a devastating disorder caused by loss of functional dystrophin protein, resulting in muscle wasting. Enhancing muscle growth by inhibiting myostatin, a growth factor negatively regulating skeletal muscle mass, is a promising approach to slow disease progression. Direct administration of myostatin propeptide, a natural inhibitor of mature myostatin, has shown limited efficacy probably due to low serum stability. Here, we demonstrate that serum stability, delivery efficiency and efficacy of propeptide can be significantly enhanced by anchoring propeptide to the surface of exosomes by fusing the inhibitory domain of myostatin propeptide into the second extracellular loop of CD63 (EXOpro). Repeated administrations of EXOpro accelerated muscle regeneration and growth, resulting in significantly increased muscle mass and functional rescue without any detectable toxicity in mdx mice. Importantly, EXOpro partially rehabilitated bone structure and promoted bone regeneration in mdx mice. Our findings demonstrate that anchoring to exosomes increased delivery and serum stability of propeptide and augmented the inhibitory efficacy of myostatin propeptide and thus provide a delivery platform for propeptide-based intervention in DMD.